Reversal of economic integration: Evidence from EU enlargement - Hinnerk Gnutzmann; Arevik Gnutzmann-Mkrtchyan; Tobias Korn (Leibniz-Institut für Ost- und Südosteuropaforschung (IOS), 2025)
Empirical models of trade agreements implicitly assume that withdrawal from a trade agreement has an equal and opposite trade effect as accession, i.e., symmetry. With increasing opposition to international economic cooperation, it becomes urgent to test this assumption. We analyze a quasi-natural experiment to explicitly test the symmetry assumption in the context of FTA termination using the gravity model. In 2004, Estonia joined the European Union, which mandated that it withdraws from its FTA with Ukraine. Carefully controlling for possible confounding effects of EU enlargement using a variety of methods, we isolate the FTA withdrawal effect and find strong support in favour of symmetry. Moreover, while import tariffs are part of the impact, the bulk of the effect comes from non-tariff effects of an FTA. General equilibrium estimates suggest that the FTA withdrawal led to a noticeable loss in members' welfare.
Keywords: F13; F14; F15; F17; 330; free trade agreement; withdrawal; gravity; welfare analysis; European Union; Estonia; Ukraine